Expression of human papillomavirus L1 protein and NuMA1 at cervical intraepithelial neoplasia - V. A. Ershov; A. S. Lisyanskaya; G. M. Manikhas (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2019)
Relevance. Cervical cancer – one of malignant new growths most often met among women. Intraepithelial changes precede to it; these changes can disappear spontaneously or progress to cancer. For the present moment, there are no markers describing the outcome of cervical intraepithelial neoplasia.The objective was to research the expression L1 HPV and NuMA1 as factors of prognosis HPV-positive cervical intraepithelial neoplasias by high-risk human papillomavirus.Material and methods. The biopsies of 178 women from HPV-positive cervical neoplasias were studied by cytological, histological, immunocytochemical methods and PCR.Results. We verified HPV-HR-positive: mild (42.7 %), moderate (34.27 %), severe (21.91 %) dysplasias, Ca in situ (1.12 %). In 81.13 % of researches, CIN with expression of L1 and NuMA1 had regression of dysplasia, in 13.21 % – persistence of grade squamous intraepithelial lesion, in 5.66 % – progression of dysplasia. In 73.33 % of cases, CIN with expression of NuMA1 had regression, in 26.67 % – persistence of dysplasia. In 45.45 % of researches, CIN with expression of L1 had regression of dysplasia, in 48.48 % – persistence of grade squamous intraepithelial lesion, in 6.06 % – progression of dysplasia. Regression or progression of dysplasia with expression L1 and NuMA1 or one of these proteins for the first time was revealed later 6 months.Conclusion. CIN could come to the end with regression, persistence or progression. At expression of atypical cells L1 and NuMA1, the greatest quantity – 81.13 %, of cases of CIN regression was noted. At expression of atypical cells only NuMA1, CIN came to the end with regression or long persistence. Course of CIN with expression L1 HPV was characterized by the greatest parameters of persistence and progression marked, accordingly, in 48.48 and 6.06 % of cases.